The Influence of Replacing Fish Meal Partially in Diet With Soybean Meal and Full-fat Soya on Growth and Body Composition of Rainbow Trout (Oncorhynchus mykiss) - Harlioglu, Ayse Gul (Zoological Soc Pakistan, 2011)
Rainbow trouts were fed for five months with iso nitrogenous (average 50 36 % crude protein) diets in which dietary protein was supplied by fish meal (FM) soybean meal (SBM) or full tat soy a (ITS) Diet 1 (control diet) contained 43% FM and 25% SBM Those of experimental diets were 28% FM and 40% SBM for Diet 2 13% FM and 55% SBM for Diet 3 28% FM and 40% IFS for Diet 4 and 13% FM and 55% FFS for Diet 5 respectively It was found that an increase in plant protein in diets adversely affected growth performance and teed conversion ratio (FCR) in rainbow trout It was also found that the fish fed with the diet containing IFS had signiticantly higher FCR than the fish fed with SBM (P<0 05) In comparison control diet to fish fed with Diet 2 and 3 there welt, no significant differences (P>0 05) in body protein content In addition the lowest cost to produce 1 kg fish can be obtained from experimental Diet 2 1 here was not a significant (P>0 05) difference in specific growth rate protein efficiency ratio protein productive value, lipid productive value, energy productive value and FCR between control diet and Diet 2 and SBM can be used up to 40% in rainbow trout growth rations In conclusion this study showed that Diet 2 is optimum for rainbow trout
Keywords: rainbow trout; Oncorhynchus mykiss; soy bean meal; full fat soy bean meal growth nutrition